2005
DOI: 10.1560/9qtd-b1gj-k8j7-7yjr
|View full text |Cite
|
Sign up to set email alerts
|

Formation and applications of stable 10 nm to 500 nm supramolecular porphyrinic materials

Abstract: Nanoscaled materials of organic dyes are of interest for a variety of potential applications because of the rich photonic properties that this class of molecules can impart. One mode to form such nanoscaled materials is via self‐organization and self‐assembly, using reasonably well understood methods in supramolecular chemistry. But there are inherent complexities that arise from the use of organic‐based supramolecular materials, including stability toward dioxygen, structural stability, and nanoarchitectures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
62
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 147 publications
0
62
0
Order By: Relevance
“…The interest in this class of compounds is deter mined by the peculiarity of the electronic structure of the aromatic system of phthalocyanine, which is as fol lows: the aromatic core in the phthalocyanine molecule is planar and sufficiently large (about 2 nm 2 ) [1]. Intro ducing additional nitrogen atoms makes the interac tions between the neighboring macrorings in columns stronger, which results in the larger rigidity of the Pc columns and the whole system [28].…”
Section: Phthalocyanines As Promising Materials For Modern Engineerinmentioning
confidence: 99%
See 2 more Smart Citations
“…The interest in this class of compounds is deter mined by the peculiarity of the electronic structure of the aromatic system of phthalocyanine, which is as fol lows: the aromatic core in the phthalocyanine molecule is planar and sufficiently large (about 2 nm 2 ) [1]. Intro ducing additional nitrogen atoms makes the interac tions between the neighboring macrorings in columns stronger, which results in the larger rigidity of the Pc columns and the whole system [28].…”
Section: Phthalocyanines As Promising Materials For Modern Engineerinmentioning
confidence: 99%
“…When substituted phthalocyanines are used, there appears a possibility of extending the delocalized π electron system of the macroring, which results in more substantial structuring of the supramolecular ensemble [1]. As a result, Pc based mesogens with a noticeable thermal stability can be produced.…”
Section: Phthalocyanines As Promising Materials For Modern Engineerinmentioning
confidence: 99%
See 1 more Smart Citation
“…A formation of nanometer orde (10-500 nm) discrete material is a key issue for a various application technology in the future [29]. A discrete surface morphology of zinc porphyrin has been reported that can be controlled by varying the concentration as well as deposition parameters [30].…”
Section: Introductionmentioning
confidence: 99%
“…The metal ions in these complexes are oxophilic; thus, the preference for carboxylate or other oxygen-bearing anionic ligands. Zr(IV) has an electron configuration of [Kr]4f 14 , is closed shell metal ion and Because of the lack of functional groups on the porphyrin moieties, there is a paucity of supramolecular materials with designed, hierarchical structures [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] containing Zr(Por). The key entry to the organometallic zirconium porphyrin complexes would be Zr-(Porphyrin)Cl 2 , analogous to ZrCp 2 Cl 2 .…”
mentioning
confidence: 99%